Epidemic, risk factors of carbapenem-resistant Klebsiella pneumoniae infection and its effect on the early prognosis of liver transplantation - Liu, Ning; Yang, Gengxia; Dang, Yan; Liu, Xin; Chen, Ming; Dai, Fangfang; Ding, Xiurong; Li, Wenlei; Li, Guangming; Lou, Jinli; Chen, Dexi; Yu, Yanhua (Frontiers in Cellular and Infection Microbiology, 2022)
Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) infection remains a major cause of morbidity and mortality in early-stage post-liver transplantation (LT). Methods We retrospectively analyzed the demographic and clinical infections characteristics of all LT recipients in our hospital between January 2019 and December 2021. Results Among the 272 LT recipients who received LT between January 2019 and December 2021, sixty-two patients had at least one infection within 3-months post-LT, with a prevalence of 22.8% (62/272). The prevalence of CRKP infections was 7.0% (19/272), and the 3-months post-LT mortality was 19.4% (12/62). The risk factors independently related to 3-months mortality were age (Odds ratio (OR)= 1.126, 95% Confidence interval (CI): 1.009~1.257; P=0.034), mechanical ventilation (MV) (OR=1.206, 95% CI: 1.039~1.401; P =0.014), and CRKP infection (OR=18.240, 95% CI: 2.206~150.842; P =0.007). In CRKP infection, the length of ICU stay (OR=1.067, 95% CI: 1.015~1.122; P=0.011), pre-operation infection (POI) (OR=6.733, 95% CI: 1.160~39.088; P=0.034), and hepatocellular carcinoma (HCC) (OR=26.772, 95% CI: 1.747~410.187; P=0.018) were the independent risk factors. With COX multivariate regression analysis, the 3-months survival rate of CRKP infected patients was significantly lower than that without CRKP infection post-LT. Conclusions CRKP infection is closely correlated with poor prognosis in 3-months post-LT.